Applications of nonlinear optics in ultrashort pulse metrology and vice versa - Walmsley, I; Kosik, E; Dorrer, C; Boyd, R; Piredda, G; IEEE; IEEE (2002)
We discuss recent developments in the characterization of ultrashort optical pulses in the space-time domain and the attosecond regime. These methods may be applied to the study of the dynamics of the field in nonlinear interactions.